Estudo de receptores colinérgicos muscarínicos e da atividade acetilcolinesterasica em cérebro de pacientes idosos com demência - Miranda, Maira Di Ciero (1991)
In spite oF cholinergic System being enough explored by various workers in the investigation oF Alzheimer's disease, still exist considerable discrepancies in the results related to cholinergic alterations particulary in respect to receptor number, needing more detailed studies. On the other hand, we con not exclude the involvement oF other neurotransmitter systems For a real underst anding oF this complex pathology that aFFects nearly 5 to 15% oF the population aged 65 years or older. In the present work, alteration in central cholinergic System were studied utilizing homogenates oF brain tissue From six demented patients (75-95 years) From a nursing home in Fortaleza-CE (Brasil) and FiFteen Controls (69-108 years) From University Hospital. Alzheimer's disease patients were diagnosed based on screening tests (IMC - InFormation, Memory and Concentration, and SET test), clinicai Follow up, neurological evaluation and histologic analysis oF brain cortex. We analysed the acety1cholinesterase activity, muscarinic receptor number and protein concentraiion in six brain areas ( precentral gyrus, postcentral gyrus, hippocampus, caudate nucleus, lentiForm nucleus and substantia inominata). The histologic analysis oF brain cortex ( temporal, Frontal and parietal) detected the presence oF neuroFibri11 ary tangles in patients with Alzheimer's disease, although this Finding is not pathognomonic o-F this disease. We observed an increase of muscarinic receptora only in hippocampus and in substantia inominata, suggesting a compensatory mechanism or manifestation of denervation supersensitivity. The cholinergic enzyme activity was significantly reduced in hippocampus and in caudate nucleus, with a tendecy for reduction also in other areas studied.